Construction of social reality by citizen participation in social media and by media discourse - Rodriguez, Malvina Eugenia; Theiler, Elizabeth (Universidad Nacional de Villa María, 2016)
This research analyzes the construction of social reality by citizen participation in new visual environments and its role provided in media discourse in Cordoba province, Argentina from 2013 to 2015.  Three cities: Cordoba, San Francisco and Villa María were taken as case study. The research tries to identify, systematize and describe new ways of citizen communication and participation, which imply the building of socio-digital realities. The layout of the public space taking into account the promotion that private, individual and group discourse gain through social media and virtual environments, while media covering participates rebuilding these environments and so, the citizen participation channels in the public area. Therefore, citizen discourse in virtual environments as well as media discourse will be analyzed in these three cities, taking the recognition of citizen participation in events of high social significance as central point. Construction of reality from these discourses is regarded as antagonist, by shaping multiple realities in constant competition. This project expects to contribute to the theoretical debate about the matter, as well as to provide with a better knowledge of media and citizen participation in virtual environments.